PSSA- INTERNATIONAL SOLUTION TO PROTECT THE BIODIVERSITY IN HA LONG BAY - CAT BA MARINE AREA - Toan, Du Van; Dat, Le Duc; Ha, Phan Nguyen Hai; Anh, Tran Thi Tu; Anh, Le Tuan; Tien, Do Duc; Khanh, Le Vu; Hieu, Dao Huu; Thuong, Trinh Thi Thuong (Vietnam Journal of Marine Science and Technology, 2018)
A Particularly Sensitive Sea Area (PSSA) is an important management tool for biodiversity protection of a marine area. At the time of designation of a Particularly Sensitive Sea Area, an associated protective measure, which meets the requirements of the appropriate legal instrument establishing such measure, must have been approved or adopted by IMO to prevent, reduce, or eliminate the threat or identified vulnerability. Information on each of the Particularly Sensitive Sea Areas (PSSAs) that has been designated by IMO is available on the nautical chart. The Vietnam’s coastal zones and islands are the isolated oceanic habitat of extremely rich marine life in very good condition which is important to the maintenance and dispersal of the marine life of the western tropical Pacific. Vietnam coastal areas are very high risk areas affected by maritime activities, particularly international shipping, therefore in the future identification of some Particularly Sensitive Sea Areas (PSSAs) is necessary. The first Particularly Sensitive Sea Area for Vietnam in Ha Long - Cat Ba was initially proposed in this paper.